EFEKTIVITAS KONSELING KELOMPOK TEKNIK ASERTIVE TRAINING UNTUK MENURUNKAN STRES AKADEMIK SISWA - Syam, Fuadil Munawwar; Ardimen; Wahidah Fitriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Academic stress is one of the psychological problems frequently experienced by students due to academic demands, workload, and achievement pressures. If not properly addressed, this condition may negatively affect students’ concentration, emotional well-being, and academic performance. This study aimed to examine the effectiveness of group counseling using assertive training techniques in reducing students’ academic stress. The research employed a quasi-experimental design with a pretest-posttest control group design. The participants consisted of 20 students who were divided into an experimental group and a control group. The instrument used was an academic stress scale that had been tested for validity and reliability. Data were analyzed using the Independent Samples t-Test. The results revealed a significance value of 0.048 (p < 0.05), indicating a significant difference between the experimental and control groups after the intervention. Descriptively, the experimental group showed a greater reduction in academic stress scores compared to the control group. These findings indicate that group counseling with assertive training techniques is effective in reducing students’ academic stress.